Pengaruh Kualitas Produk, Lokasi Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Kedai Seblak Mama Tuti Kota Bengkulu - Desti Hendayani; Nia Indriasari; Abdul Rahman (Journal of Indonesian Management, 2023)
Kedai Seblak Mama Tuti, Bengkulu City, is one of the culinary businesses in the city of Bengkulu and is currently developing and is in great demand by consumers. The aim of this research is to determine the influence of product quality, location and service quality on purchasing decisions at Kedai Seblak Mama Tuti, Bengkulu City. The sample in the research was 70 consumers who purchased seblak at Mama Tuti's Seblak Store, Bengkulu City. Data were collected using a questionnaire and the analysis methods used were multiple linear regression, determination tests and hypothesis tests. The results of the regression analysis show Y = 7.749 + 0.257X1 + 0.370 X2 + 0.205X3. This illustrates a positive regression direction, meaning that there is a positive influence between X1 (product quality), X2 (location) and X3 (service quality) on purchasing decisions (Y). This means that if the variables of product quality, location and service quality increase, it will increase purchasing decisions at the Seblak Mama Tuti shop, Bengkulu City. The coefficient of determination is 0.570. This means that X1 (product quality), X2 (location) and X3 (service quality) influence purchasing decisions (Y) by 57%. Meanwhile, the remaining 43% is influenced by other variables not examined in this research. The results of the t test at a significance level of 0.05 explain that partially (individually) the variables location, product quality and service quality have a significant influence on the purchasing decision variable because the significant value is smaller than 0.05. The results of the F test at a significance level of 0.05 explain that the variables location, product quality and service quality have a simultaneous (together) influence on purchasing decisions because the significant value is smaller than 0.05.